Pengaruh Model Make A Match Berbantu Kartu Bergambar Terhadap Hasil Belajar IPS Tema Kayanya Negeriku Di Kelas IV SDN No 105361 Lubuk Cemara - Cindy Pratiwi, Umar Darwis (Cybernetics: Journal Educational Research and Social Studies, 2021)
This study aims to determine the results of social studies learning using a make a match model with the help of picture cards. This is shown from the results of the calculation of the posttest hypothesis test through the t-test at a significance level of 0.05, where tcount > ttable (4.25>1.994437) This result is strengthened by the achievement of the average score of students in the conventional learning class with the value of 76.2 while the make a match model obtained a value of 88.97. These results indicate that student activities can be categorized very well in using the make a match model with the help of picture cards.